Preparation method of polythiol compound and optical resin lens

By controlling the sulfide and polysulfide content in thiourea, the obtained polythiol compound color is stable, which solves the problem of unstable polythiol compound color in the prior art, and improves the quality of optical resin lenses and stability.

CN119462449APending Publication Date: 2025-02-18EFIRM NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411704230.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing polythiol compounds have poor color stability, resulting in high yellow index and unstable optical resin lenses, affecting the passing rate of overall quality.

Method used

By controlling the total content of sulfide and polysulfide in thiourea, the polysulfide content is <0.5%, and mixed with polyol and thiourea in hydrochloric acid environment, the polythioalcohol compound obtained is hydrolyzed, which significantly reduces the generation of by-products and increases the long-term coloration of the color Storage stability.

Benefits of technology

It significantly improves the long-term storage stability of the chromaticity of polythiol compounds, reduces the yellow index of optical resin lenses, improves the quality stability of the lenses, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a polythiol compound and an optical resin lens, and belongs to the technical field of new organic materials. The preparation method of the polythiol compound comprises the following steps: mixing polyhydric alcohol as shown in a formula 1, thiourea and hydrochloric acid for reaction, and hydrolyzing to obtain the polythiol compound as shown in a formula 2, wherein the total content of sulfides and polysulfides in the thiourea is less than 0.5%. According to the preparation method, by-products are reduced by controlling the total content of sulfides and polysulfides in the raw material thiourea, so that the long-term storage stability of the chromaticity of the polythiol compound is improved. An optical resin lens prepared from the polythiol compound is stable and qualified in yellow index, low in cost, suitable for large-scale industrial production and capable of meeting increasing social requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new organic materials, and in particular to a preparation method of a polythiol compound and an optical resin lens. Background Art

[0002] Compared with optical glass lenses, optical resin lenses have the advantages of being light, not easy to crack, able to be dyed, strong in anti-fogging and anti-denting. Polythiourethane optical resin lenses have excellent properties of high transparency, low yellowness, high heat resistance, high strength, high refractive index and high Abbe number, and are particularly suitable for the production of medium and high refractive index optical resin lenses. The yellow index is an important indicator of optical resin lens materials, and the key to determining the yellow index of optical resins is the chromaticity of polythiol compounds, but the long-term storage stability of the chromaticity of polythiol compounds has always been poor.

[0003] Among them, CN101400648A discloses a polythiol compound shown in Formula 2, and records its preparation method including: 2-mercaptoethanol and an epihalohydrin compound are first reacted to obtain a polyol, then the polyol is reacted with thiourea under a hydrochloric acid environment, and finally a hydrolysis reaction is carried out under ammonia water.

[0004]

[0005] However, further research revealed that the chromaticity of the compound of Formula 2 fluctuates and has poor stability, which makes the optical resin lenses produced using it have a high yellow index and poor stability, and thus makes the overall quality pass rate of the optical resin lenses low. Therefore, it is urgent to further improve the long-term storage stability of the chromaticity of the polythiol compound shown in Formula 2, so as to improve the quality of the optical resin lenses. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing a polythiol compound and an optical resin lens. The chromaticity of the polythiol compound prepared by the preparation method has long-term storage stability.

[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The present invention provides a method for preparing a polythiol compound, comprising the following steps:

[0009] The polyol represented by Formula 1, thiourea and hydrochloric acid are mixed and reacted, and hydrolyzed to obtain the polythiol compound represented by Formula 2;

[0010] Wherein, the total content of sulfide and polysulfide in the thiourea is less than 0.5%;

[0011]

[0012] In the above preparation method of the present invention, the polyol shown in Formula 1, thiourea and hydrochloric acid are mixed and reacted to obtain isothiourea salt. Then, the isothiourea salt is hydrolyzed to obtain the polythiol compound.

[0013] The addition form of the hydrochloric acid is not particularly limited, and is preferably a hydrochloric acid aqueous solution, and the concentration of the hydrochloric acid aqueous solution is preferably 10wt%-80wt%; more preferably 20wt%-50wt%. In some specific embodiments of the present invention, the concentration of the hydrochloric acid aqueous solution is 36wt%.

[0014] The molar ratio of the hydrochloric acid in the hydrochloric acid aqueous solution to the polyol represented by formula 1 is 1:(1-6); more preferably 1:(2-5).

[0015] The molar ratio of the thiourea to the polyol represented by formula 1 is 1:(1-6); more preferably 1:(2-4).

[0016] The temperature of the mixed reaction is 70°C to reflux temperature; more preferably 80°C to 120°C.

[0017] The mixing reaction time is preferably 1-24 hours.

[0018] The hydrolysis is preferably alkaline hydrolysis. More preferably, the hydrolysis solution is selected from aqueous ammonia.

[0019] The concentration of the aqueous ammonia is preferably 10 wt%-30 wt%.

[0020] The molar ratio of the aqueous ammonia to the polyol represented by Formula 1 is preferably 1:(1-10); more preferably 1:(4-7); further preferably 1:(3-6).

[0021] The hydrolysis temperature is preferably 10°C-80°C, and the time is preferably 1-10h.

[0022] The above preparation method controls the total content of sulfide and polysulfide in thiourea to less than 0.5%, significantly reducing the generation of by-products, which have extremely high chromaticity and are difficult to remove, thereby resulting in high chromaticity of polythiol compounds. The present invention reduces the total content of sulfide and polysulfide in thiourea, inhibits the formation of by-products, and thus significantly improves the long-term storage stability of the chromaticity of the thiol compound.

[0023] Preferably, the total content of sulfide and polysulfide in the thiourea is less than 0.1%; more preferably less than 0.05%; further preferably less than 0.02%; and further preferably less than 0.005%.

[0024] Furthermore, the sulfide or polysulfide can be determined by chemical titration.

[0025] The present invention does not specifically limit the method for reducing the total content of sulfide or polysulfide, and the methods include thiourea crystal controlled water washing, thiourea crystal low concentration acid solution washing, recrystallization, thiourea crystal crystal control, etc., which are well known to those skilled in the art.

[0026] Preferably, the chemical formulas of the sulfide and polysulfide are respectively expressed as (M) n S m , wherein M is selected from Fe 2 + 、Na + , K + , Mn 2+ , Ca 2+ or NH4 + , n is selected from 1 or 2, and m is selected from an integer between 1 and 8. In the above preparation method, the polyol represented by Formula 1 is prepared by reacting 2-mercaptoethanol with an epichlorohydrin compound in an alkaline solution.

[0027] The 2-mercaptoethanol can be purchased or made by oneself, and the iron content thereof is below 10 ppm.

[0028] The alkaline solution is selected from sodium hydroxide solution, ammonia water, potassium hydroxide solution, sodium carbonate solution and the like.

[0029] The method for preparing the polyol represented by Formula 1 is preferably:

[0030] 1) adding a sodium hydroxide solution dropwise to 2-mercaptoethanol having an iron content of less than 10 ppm to form a mixed solution 1;

[0031] 2) Epichlorohydrin is added dropwise to the mixed solution 1 to obtain a polyol represented by formula 1.

[0032] The molar ratio of 2-mercaptoethanol to epichlorohydrin is (0.1-1):1; more preferably (0.3-0.7):1; further preferably (0.4-0.6):1.

[0033] The molar ratio of sodium hydroxide to 2-mercaptoethanol in the sodium hydroxide solution is (0.1-1):1; more preferably (0.3-0.8):1.

[0034] The time for adding the sodium hydroxide solution dropwise in the above step 1) is preferably 0.5-6 hours.

[0035] After the reaction in the above step 2) is completed, a heat preservation reaction can be carried out.

[0036] The insulation reaction time is 0.5-10h.

[0037] The reaction temperature is preferably 0°C-100°C.

[0038] The present invention also provides a polythiol compound prepared by the above-mentioned preparation method.

[0039] Preferably, the chromaticity value of the polythiol compound is 2.5-3.8, more preferably 2.5-2.7. In some specific embodiments of the present invention, preferably 2.5, 2.6 or 2.7.

[0040] Preferably, the chromaticity value change rate of the polythiol compound after storage for 300 days is ≤45%; more preferably, the chromaticity value change rate of the polythiol compound after storage for 300 days is ≤25%. In some specific embodiments of the present invention, the chromaticity value change rate of the polythiol compound after storage for 300 days is 4%, 23% or 44%.

[0041] The present invention also provides an optical resin lens, which is prepared by curing a resin matrix and the above-mentioned polythiol compound.

[0042] Preferably, the resin matrix is ​​selected from isocyanate.

[0043] The optical resin lens is a polythiourethane optical resin lens.

[0044] The isocyanate includes, but is not limited to, tetramethylene diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, 4,4'-diisocyanate dicyclohexylmethane, isophorone diisocyanate, norbornane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, tetramethyl-m-xylylene diisocyanate, dipropyl disulfide, diethyl disulfide, 2,5-diisocyanatomethylthiophene, 2,5-diisocyanatomethyl-1,4-dithiane, 2, 5-diisocyanate-1,4-dithiane, dihexyl thiodiisocyanate, dipropyl thiodiisocyanate, bis(isocyanatomethyl)adamantane, bis(isocyanatomethyl)tetrahydrothiophene, 2,6-bis(isocyanatomethyl)naphthalene, 1,5-naphthalene diisocyanate, diethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine triisocyanate, toluene diisocyanate, o-tolidine diisocyanate, diphenylmethane diisocyanate, diphenyl ether diisocyanate, triphenylmethane triisocyanate, etc.

[0045] Preferably, the isocyanate is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, norbornane diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, m-phenylenediisocyanate, and hydrogenated m-phenylenediisocyanate; more preferably, it is one or more of hydrogenated m-phenylenediisocyanate, norbornane diisocyanate, and m-phenylenediisocyanate; further preferably, it is hydrogenated m-phenylenediisocyanate or m-phenylenediisocyanate. Preferably, the molar ratio of the thiol group in the polythiol compound to the isocyanate group or isothiocyanate group in the resin matrix is ​​(0.5-3):1; more preferably, it is (0.6-2):1; further preferably, it is (0.8-1.3):1.

[0046] The resin matrix and the polythiol compound within the above-mentioned ratio range enable the optical resin lens to have better physical properties, operability and polymerization reactivity.

[0047] The optical resin lens of the present invention has high refractive index and high heat resistance.

[0048] The raw materials for the curing reaction further include one or more of a catalyst, a release agent, an ultraviolet absorber, and a toner.

[0049] The catalyst is selected from one or more of dibutyltin dilaurate, dibutyltin dichloride, dibutyltin oxide, and stannous octoate; more preferably, dibutyltin dilaurate or dibutyltin dichloride.

[0050] When the catalyst addition amount is less than 0.001%, the polymerization may be incomplete, resulting in poor mechanical formation of the optical resin lens. When the catalyst addition amount is greater than 0.3%, the polymerization speed may be too fast, resulting in an increase in the color tone of the optical resin lens.

[0051] The catalyst addition amount is preferably 0.001wt%-0.3wt% of the content of the optical resin lens, more preferably 0.01wt%-0.1wt%, further preferably 0.01wt%-0.05wt%.

[0052] The above-mentioned release agent, ultraviolet absorber and toner are all additives for conventional optical resin lenses, which are used to improve the performance of the optical resin lenses.

[0053] The chromaticity of the optical resin lens can be evaluated based on the YI value specified in JIS K7373: 2006, for example. The smaller the YI value, the less coloring. The YI value of the optical resin lens of the present invention is 1.50-2.

[0054] The optical resin lens of the present invention has the advantages of low chroma and strong long-term storage stability.

[0055] The curing reaction between the polythiol compound and the resin matrix can be carried out by various conventional curing treatments.

[0056] For example, in order to prepare a cured product having a lens shape, cast polymerization is preferred.

[0057] In the cast polymerization, a curing reaction raw material is injected into a cavity of a mold sealed with a tape, and a curing reaction is carried out in the cavity to obtain a cured product (polythiourethane type optical resin lens).

[0058] The curing reaction temperature is preferably 100°C-170°C.

[0059] After the curing reaction is completed, the temperature is lowered and the mold is demolded to obtain a solidified product in the shape of the inner part of the mold cavity. The solidified product is preferably used as a lens substrate for optical resin eyeglass lenses.

[0060] After the above-mentioned demolding, the process also includes annealing, grinding (such as rounding), and lapping, which are used to improve the impact resistance of the base coating, the surface hardness of the hard coating, and other post-coating processes, so as to better form various functional layers such as anti-reflection layer and water-repellent layer on the surface of the optical resin lens substrate.

[0061] The present invention also provides the use of the optical resin lens in myopia lenses or corrective eyeglass lenses.

[0062] Compared with the prior art, the preparation method of the polythiol compound provided by the present invention comprises the following steps: mixing the polyol shown in Formula 1, thiourea and hydrochloric acid for reaction, and hydrolyzing to obtain the polythiol compound shown in Formula 2; wherein the total content of sulfide and polysulfide in the thiourea is less than 0.5%. The preparation method of the present invention reduces by-products by controlling the total content of sulfide and polysulfide in the raw material thiourea, thereby improving the long-term storage stability of the chromaticity of the polythiol compound of the present invention. The optical resin lens prepared by the polythiol compound of the present invention has a stable and qualified yellow index, reduced cost, is suitable for large-scale industrial production, and can meet the growing social needs. DETAILED DESCRIPTION

[0063] In order to further illustrate the present invention, the preparation method of the polythiol compound and the optical resin lens provided by the present invention are described in detail below in conjunction with examples.

[0064] Unless otherwise specified, the raw materials used in the following examples are all commercially available products.

[0065] The specific evaluation methods used in the following examples include the following:

[0066] (1) Sulfide and polysulfide content in thiourea

[0067] Detection method of sulfide content in thiourea:

[0068] 1. Determination of sulfide content in thiourea

[0069] 1.1 Method Summary

[0070] The sulfide in thiourea reacts with cadmium acetate to generate yellow cadmium sulfide precipitate, that is, the sulfide in the sample is completely separated by using excess cadmium acetate. The reaction is as follows:

[0071] 2S 2- +2(CH3COO)2Cd=2CdS↓+2(CH3COO) 2- +2CH3COOH

[0072] After the CdS precipitate is dissolved by hydrochloric acid, it reacts quantitatively with iodine. The excess iodine is titrated with a sodium thiosulfate standard titration solution (back titration method). The reaction process is as follows:

[0073] CdS+2HCl+I2=S+CdCl2+2HI

[0074] 2Na2S2O3+I2=Na2S4O6+2NaI

[0075] 1.2 Reagents

[0076] 1.2.1 Cadmium acetate solution: 1.5%.

[0077] 1.2.2 Hydrochloric acid solution: 1+2 (refers to preparing hydrochloric acid solution by mixing concentrated hydrochloric acid and water in a weight ratio of 1:2).

[0078] 1.2.3 Iodine standard titration solution: c(1 / 2I2)=0.1mol / L.

[0079] 1.2.4 Sodium thiosulfate standard titration solution: c(Na2S2O3) = 0.1 mol / L.

[0080] 1.2.5 Starch indicator solution: 10g / L.

[0081] 1.3 Instruments and Equipment

[0082] 1.3.1 Circulating water vacuum pump.

[0083] 1.3.2 Filter bottle.

[0084] 1.3.3 Buchner funnel.

[0085] 1.4 Analysis steps

[0086] Take 1g of sample and dissolve it in pure water, then dilute it into a 100mL volumetric flask as a test sample.

[0087] After the sample is dry-filtered with filter paper, draw 5.00 mL of the filtrate into a 100 mL volumetric flask, dilute to scale with water, and mix. Draw 5.00 mL of the above dilution into a 250 mL iodine volumetric flask, add a certain amount of cadmium acetate solution, rinse the flask wall with water, mix to make the reaction complete, and pour into a Buchner funnel covered with filter paper for suction filtration, rinse the flask wall with water to transfer all the precipitate to the suction filtration flask.

[0088] Take out the filter paper with yellow precipitate, put it into the original iodine volumetric bottle, add iodine standard titration solution and hydrochloric acid solution, quickly plug it and shake it vigorously until the filter paper is completely broken, and use a small amount of water to rinse the attached liquid on the bottle stopper and bottle mouth into the bottle. Titrate with sodium thiosulfate standard titration solution. When it is close to the end point, add 2mL~3mL starch indicator solution, continue to titrate until the blue color disappears and does not change color within 30s, and record the volume of sodium thiosulfate standard titration solution V1 consumed.

[0089] At the same time, a blank test is carried out using water instead of the sample, and the volume V0 of the sodium thiosulfate standard titration solution consumed is recorded.

[0090] The required solution volume mentioned above should comply with the requirements in Table 1.

[0091] Table 1 Solution volume requirements

[0092]

[0093] 1.5 Expression and calculation of results

[0094] The mass-volume concentration w1 of sulfide in thiourea, expressed in g / L, is calculated according to formula (1):

[0095] w1=(V0-V1)×c×M.............(1)

[0096] In the formula: V0 is the volume of sodium thiosulfate standard titration solution consumed by the blank test, in milliliters (mL); V1 is the volume of sodium thiosulfate standard titration solution consumed by the sample, in milliliters (mL); c is the accurate concentration of sodium thiosulfate standard titration solution, in moles per liter (mol / L); M is the molar mass of sulfide [MS], in grams per mole (g / mol).

[0097] The arithmetic mean of the parallel determination results is taken as the determination result, and the absolute difference of the parallel determination results is not greater than 0.5%. The final result value is retained to two decimal places. The calculation of the results is carried out in accordance with the provisions of GB / T 8170.

[0098] 2. Detection method of polysulfide content in thiourea:

[0099] 2.2 Spectrophotometry

[0100] 2.2.3 Method Summary

[0101] Under acidic conditions, the thiocyanate in the sample complexes with trivalent iron ions to make the solution appear red. The absorbance of the complex is measured at the maximum absorption wavelength of 460nm using a spectrophotometer. The thiourea thiocyanate content is measured as S1. After adding a small amount of potassium ferrocyanide, polysulfide reacts with potassium ferrocyanide to generate thiocyanate. The thiocyanate content is measured again as S2, and the polysulfide content can be calculated.

[0102] 2.2.4 Reagents

[0103] 2.2.4.1 Hydrochloric acid solution: 1+2 (refers to preparing hydrochloric acid solution by mixing concentrated hydrochloric acid and water in a weight ratio of 1:2).

[0104] 2.2.4.2 Hydrochloric acid solution: 20%

[0105] 2.2.4.3 Ethanol: 95%.

[0106] 2.2.4.4 Ammonium ferric sulfate solution: 100 g / L. Weigh 10 g of ammonium ferric sulfate [NH4Fe(SO4)2·12H2O], dissolve it in 50 mL of water containing 1 to 2 drops of sulfuric acid, and dilute to 100 mL.

[0107] 2.2.4.5 Ammonium ferric sulfate plus potassium ferrocyanide solution: 100 g / L. Weigh 10 g of ammonium ferric sulfate [NH4Fe(SO4)2·12H2O], dissolve it in 50 mL of water containing 1 to 2 drops of sulfuric acid, and add 0.2 g of potassium ferrocyanide to dilute to 100 mL.

[0108] 2.2.4.6 Thiourea without thiocyanate: Weigh about 100g of thiourea, place it in a 500mL beaker, add 300mL of water, heat to dissolve, filter, cool rapidly, precipitate crystals, filter with a sand core funnel, and wash twice with 100mL of ethanol. Dissolve the crystals in 100mL of water, and treat them again according to the above method to obtain the second crystals. Dissolve the second crystals in 50mL of water, and treat them again according to the above method to obtain the third crystals. Dry the third crystals in a 50℃±2℃ electric blast drying oven for 1h, and cool them in a desiccator containing silica gel desiccant for use.

[0109] 2.2.4.7 Thiocyanate (CNS) impurity standard solution: 0.1 mg / mL.

[0110] 2.2.5 Instruments and materials

[0111] 2.2.5.1 Circulating water vacuum pump.

[0112] 2.2.5.2 Electric constant temperature drying oven: The temperature can be controlled at 105℃±2℃.

[0113] 2.2.5.3 Glass sand crucible: The pore size of the filter plate is 5 to 15 μm.

[0114] 2.2.5.4 Spectrophotometer: Equipped with a cuvette with a 1 cm optical path.

[0115] 2.2.6 Analysis steps (spectrophotometry)

[0116] 2.2.6.1 Detection of thiocyanate in thiourea

[0117] 2.2.6.1.1 Drawing of standard curve

[0118] Pipette 0.2mL, 0.5mL, 1mL, 2mL, 5mL, 10mL, and 15mL of thiocyanate standard solution into 7 100mL volumetric flasks respectively, add 2g of thiourea without thiocyanate (accurate to 0.0001g), add 20mL of water to dissolve, add 0.2mL of hydrochloric acid solution (1+2, that is, concentrated hydrochloric acid and water are prepared in a weight ratio of 1:2) and 0.5mL of ammonium ferric sulfate solution, dilute with water to the scale, shake well, and let stand for 10min.

[0119] At a wavelength of 460nm, using the blank solution without thiocyanate standard solution as a reference, measure the absorbance of the standard series solutions in sequence.

[0120] The absorbance value measured by the standard series is subtracted from the absorbance value of the blank to obtain the corrected absorbance value. A standard curve is drawn with the corrected absorbance as the abscissa and the mass of thiocyanate contained in 100 mL of the standard solution as the ordinate.

[0121] Note: When replacing the reagent ammonium ferric sulfate solution, perform a midpoint calibration. If the test value is consistent with the theoretical value, continue to use the curve; otherwise, re-establish the curve.

[0122] 2.2.6.1.2 Determination of absorbance

[0123] Weigh 2g of sample (thiourea) to an accuracy of 0.0001g, place in a 100mL volumetric flask, add 20mL of water to dissolve, add 0.2mL of hydrochloric acid solution and 0.5mL of ammonium ferric sulfate solution, dilute to scale with water, shake well, and let stand for 10min. At a wavelength of 460nm, adjust the spectrophotometer absorbance to zero with a blank solution without adding the sample, and then measure the absorbance of the solution. The thiocyanate content S1 in thiourea is calculated by the standard curve.

[0124] Weigh 2g of sample (thiourea) to an accuracy of 0.0001g, place in a 100mL volumetric flask, add 20mL of water to dissolve, add 0.2mL of hydrochloric acid solution and 0.5mL of ammonium ferric sulfate plus potassium ferrocyanide solution, dilute to scale with water, shake well, and let stand for 10min. At a wavelength of 460nm, adjust the spectrophotometer absorbance to zero with a blank solution without adding the sample, and then measure the absorbance of the solution. The thiocyanate content S2 in thiourea is calculated by the standard curve.

[0125] Result value: w = (32 / 58*S2-32 / 58*S2)

[0126] (2) Coloration evaluation of polythiol compounds (b* value)

[0127] The b* values ​​(also called chromaticity values) of the polythiol compounds obtained in Examples and Comparative Examples were measured using a spectrophotometer U-3500 manufactured by Hitachi, Ltd. at an optical path length of 10 mm.

[0128] (3) Coloration evaluation of cured product (YI value)

[0129] The YI values ​​of the cured products (0.00D, center wall thickness 1.8 mm) obtained in Examples and Comparative Examples were measured using a spectral transmittance measuring device DOT-3 manufactured by Murakami Color Research Laboratory Co., Ltd.

[0130] It was confirmed by GPC (gel permeation chromatography), HPLC (high performance liquid chromatography) and MS (mass spectrometry) that the polythiol compound represented by formula (1) was obtained in the following Examples and Comparative Examples.

[0131] Thiourea pretreatment

[0132] The sulfide or polysulfide content of the purchased or produced thiourea was measured by the evaluation method (1) above, and the result was 0.6%-0.9%. The iron content of the thiourea obtained by low-concentration pickling treatment of thiourea by the above-mentioned preparation methods of different sulfides and polysulfides was 50ppm-0.2%. In the following examples, the thioureas obtained above were used respectively.

[0133] Example 1

[0134] (1) Synthesis of the polythiol compound represented by formula 2

[0135] First, 78.2 g of 2-mercaptoethanol with a purity of 99.80 wt % was placed in a 1 L four-necked flask equipped with a stirrer, a nitrogen purge tube and a thermometer, and protected by a nitrogen flow. 65.8 g of a 32 wt % aqueous sodium hydroxide solution was added dropwise at 30° C. over 30 minutes, and then 46.3 g of epichlorohydrin was added dropwise over 1 hour, and the mixture was kept warm for 30 minutes.

[0136] Then, 200 g of 36 wt% hydrochloric acid and 130 g of thiourea (sulfide and polysulfide content of 0.02%) were added, and the mixture was refluxed at 110° C. for 3 hours to obtain isothiourea salt.

[0137] Finally, after cooling to room temperature, 250 g of 18 wt % ammonia water was added and the reaction was carried out at 55° C. for 3 hours. The mixture was allowed to stand for stratification, and the lower organic phase was separated to obtain a crude polythiol compound shown in Formula 2. Hydrochloric acid was added to adjust the pH to about 6, and water was added for two washes. The mixture was heated and decompressed to obtain a polythiol compound shown in Formula 2. The b* value of the obtained polythiol compound was 2.5, and the b* value was re-tested after storage for 300 days and was 2.6.

[0138] (2) Production of optical resin lenses

[0139] 52 parts by mass of xylylene diisocyanate, 0.01 parts by mass of dibutyltin dichloride as a curing catalyst, 0.08 parts by mass of acidic phosphate as a release agent, and 0.60 parts by mass of an ultraviolet absorber (UV329) were weighed and mixed and dissolved, and 48 parts by mass of the polythiol compound obtained in Example 1 was added thereto to obtain a mixed solution. The mixed solution was degassed at 200 Pa for 1 hour and then filtered through a PTFE (polytetrafluoroethylene) filter with a pore size of 5.0 μm.

[0140] The filtered mixed liquid (curing composition) is injected into a lens molding mold comprising a glass mold with a diameter of 75 mm and 0.00D and an adhesive tape. The molding mold is placed in an oven, and the temperature is slowly raised from 20°C to 120°C over 24 hours, and kept at 120°C for 4 hours to perform polymerization (curing reaction). After the polymerization is completed, the molding mold is taken out of the oven when the temperature drops to 60°C, and the mold is demolded to obtain a cured product (polythiourethane optical resin lens). The obtained polythiourethane optical resin lens is further annealed in an oven at a temperature of 120°C for 3 hours, and the YI value of the optical resin lens finally obtained is 1.42.

[0141] Example 2-3

[0142] The same as Example 1, the only difference is that the content of sulfide and polysulfide in thiourea is different, and the specific content is shown in Table 1. A polythiol compound and an optical resin lens are prepared.

[0143] Comparative Examples 1-3

[0144] The same as Example 1, the only difference is that the content of sulfide and polysulfide in thiourea is different, and the specific content is shown in Table 2. A polythiol compound and an optical resin lens were prepared.

[0145] Table 2 Test results of Examples 1-3 and Comparative Examples 1-3

[0146]

[0147] The results in Table 2 show that by using sulfide and thiourea with a polysulfide content of less than 0.2% in the preparation method of the above-mentioned polythiol compound, a polythiol compound with long-term stable storage chromaticity is obtained, and the chromaticity can be stabilized below 3.9 after storage for 300 days; further, by using the polythiol compound, a polythiourethane optical resin lens with a significantly reduced yellow index can be obtained.

[0148] The data of the above examples and comparative examples further verify that the polythiol compound obtained by the method for preparing the polythiol compound of the present invention has the advantages of low chroma and long-term storage stability.

[0149] The cured product (optical resin lens or polythiourethane optical resin lens) prepared using the polythiol compound of the present invention has the advantages of stable chromaticity and low yellow index, and has great application value in the preparation of various optical components such as eyeglass lenses.

[0150] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a polythiol compound, characterized in that: The following steps are involved: The polyol represented by Formula 1, thiourea and hydrochloric acid are mixed and reacted, and hydrolyzed to obtain the polythiol compound represented by Formula 2; Wherein, the total content of sulfide and polysulfide in the thiourea is less than 0.5%; 2. The preparation method according to claim 1, characterized in that: The total content of sulfide and polysulfide in the thiourea is less than 0.1%.

3. The preparation method according to claim 1 or 2, characterized in that: The chemical formulas of the sulfide and polysulfide are respectively expressed as (M) n S m , wherein M is selected from Fe 2+ 、Na + , K + , Mn 2+ , Ca 2+ or NH4 + , n is selected from 1 or 2, and m is selected from an integer between 1-8.

4. A polythiol compound, characterized in that The invention is prepared by the preparation method according to any one of claims 1 to 3.

5. The polythiol compound according to claim 4, characterized in that The chromaticity value of the polythiol compound is 2.5-3.8; The chromaticity value change rate of the polythiol compound after storage for 300 days is ≤45%.

6. An optical resin lens, characterized in that: The polythiol compound is prepared by curing reaction between a resin matrix and the polythiol compound according to claim 4 or 5.

7. The optical resin lens according to claim 6, characterized in that: The resin matrix is ​​selected from isocyanates.

8. The optical resin lens according to claim 7, characterized in that: The isocyanate is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, norbornane diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, meta-xylylene diisocyanate, and hydrogenated meta-xylylene diisocyanate.

9. The optical resin lens according to claim 7, characterized in that: The molar ratio of the thiol group in the polythiol compound to the isocyanate group or isothiocyanate group in the resin matrix is ​​(0.5-3):

1.

10. Use of the optical resin lens according to any one of claims 6 to 9 in myopia lenses or corrective lenses.

Citation Information

Patent Citations

  • Method for producing polythiol compound for optical material and polymerizable composition containing same

    CN101400648A

  • Process for production of (poly)thiol compound for use as optical material, and polymerizable composition comprising the compound

    CN101421232A

  • Preparation method for polythiol having improved storage stability

    CN112004797A

  • Method for detecting content of sulfide in electronic-grade thiourea

    CN113267461A

  • Method for producing polythiol compound for optical material

    JP2018058774A

Cited By

  • Preparation method of diethylaminoethyl isothiourea salt and preparation method of tiamulin

    CN120271487A